Graphene-based dynamic gas diffusion catalytic electrode material, preparation method and application

CN117525449BActive Publication Date: 2026-11-03NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210891244.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2026-11-03
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

The gas diffusion electrodes in existing liquid flow electrolyzers suffer from insufficient reactivity and kinetic performance due to their fixed pore size, small surface area, and poor wettability, which limits the flow of electrolytes and gases.

Method used

A graphene-based dynamic gas diffusion catalytic electrode material is used. Through a composite structure composed of hydrogel and Ag-TCNQ nanodots, the pore structure is adjusted by capillary force to form a high specific surface area and abundant active sites. Combined with a polytetrafluoroethylene membrane, the catalytic electrode is formed.

Benefits of technology

It achieves high oxygen utilization and hydrogen peroxide production performance, and has excellent activity, selectivity and durability, making it suitable for electrocatalytic reactions in flow electrolyzers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117525449B_ABST
    Figure CN117525449B_ABST
Patent Text Reader

Abstract

The application discloses a graphene-based dynamic gas diffusion catalytic electrode material, a preparation method and application, which comprises a substrate as a carrier, a graphene catalytic layer grown on the carrier and Ag-TCNQ nanodots grown on the surface of the graphene. The steps are as follows: GO is mixed with the substrate body, and is hydrothermally reduced into graphene hydrogel; the graphene hydrogel is left to stand in a silver nitrate aqueous solution for a period of time; the obtained sample is put into an NMP / H2O mixed solution for a period of time; the sample is left to stand in air for a period of time; the obtained material is put into an acetonitrile solution, an acetonitrile solution of TCNQ is added, and the sample is left to stand for a period of time, so that a composite material is obtained. The obtained material exhibits excellent electrocatalytic oxygen reduction performance; by adjusting experimental parameters, the microstructure of the electrode can be dynamically adjusted, a dense porous structure is formed, the material has the advantages of high specific surface area and low electron transmission resistance, and the material has a wide application prospect in the fields of energy and catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a graphene-based dynamic gas diffusion catalytic electrode, belonging to the field of catalytic electrode preparation technology. Background Technology

[0002] Flow electrolyzers represent an advanced, commercially viable class of reaction systems, widely used in many electrocatalytic reactions (such as oxygen reduction, water electrolysis, and fuel cells). Unlike traditional H-type electrolyzers, flow electrolyzers provide a three-phase interface of reactant gas, catalyst, and electrolyte. The flow of gas increases contact with active sites, while the flow of electrolyte rapidly removes products, shifting the reaction equilibrium to the right. The three-phase interface continuously promotes contact between oxygen molecules and active sites, thereby improving oxygen utilization. Notably, the core component of a flow electrolyzer is the gas diffusion electrode (GDE). A GDE typically consists of a gas diffusion layer and a catalyst layer forming the three-phase interface. This gas diffusion layer comprises a large-pore, conductive, and hydrophobic carbon substrate and a microporous layer of carbon particulate packing that provides gas transport. Active materials (such as Pt, Au, Pd, and Pd-Hg) are deposited on the surface of a gas diffusion layer (GDL) with the aid of a binder (such as Nafion), and then dried in air, resulting in a dehydrated form. The moisture evaporates to enhance the interaction of the active materials on the GDL. Therefore, the resulting gas diffusion layer (GDE) exhibits relatively poor wettability, fixed porosity, and a damaged surface area, restricting the flow of electrolytes and gases, thereby reducing the reactivity and kinetics of the reaction. Summary of the Invention

[0003] The purpose of this invention is to provide a graphene-based dynamic gas diffusion catalytic electrode material, its preparation method, and its application.

[0004] The technical solution to achieve the purpose of this invention is as follows: A graphene-based dynamic gas diffusion catalytic electrode material and its preparation method, comprising the following steps: Step 1: Prepare graphene hydrogel on a gas diffusion electrode substrate by hydrothermal reduction of an aqueous solution of graphene oxide (GO); Step 2: Place the graphene hydrogel obtained in Step 1 in a silver nitrate aqueous solution of a certain concentration and react for a period of time. Step 3: Place the sample obtained in Step 2 in a mixed solution of N-methylpyrrolidone (NMP) / water (H2O) (v / v) and react for a period of time; Step 4: Place the material obtained in Step 3 in the air to evaporate for a period of time; Step 5: Place the material obtained in Step 4 into an acetonitrile solution, add an acetonitrile solution of the organic ligand 7,7,8,8-tetracyano-p-benzoquinone dimethane (TCNQ), and continue to let the reaction stand for a period of time to obtain a graphene-based dynamic gas diffusion catalytic electrode material.

[0005] Furthermore, in step one, the concentration of the graphene oxide (GO) aqueous solution is 1-3 mg / mL. -1 .

[0006] Furthermore, in step one, the hydrothermal reduction reaction temperature is 140-160 ℃, and the reaction time is 4-8 h.

[0007] Furthermore, in step one, the substrate for the gas diffusion electrode includes carbon cloth, carbon felt, etc.

[0008] Furthermore, in step two, the concentration of the silver nitrate aqueous solution is 15-25 mg / mL. -1 The reaction time is 2-8 hours.

[0009] Furthermore, in step two, the mass ratio of graphite oxide to silver nitrate is 1:40-1:60.

[0010] Furthermore, in step three, the volume ratio of NMP to H2O in the NMP / H2O mixed solution is 7 / 3, and the reaction time is 2-4 hours.

[0011] Furthermore, in step four, the evaporation time is 5-12 hours, and the temperature is 15-35°C.

[0012] Furthermore, in step five, the reaction time of 7,7,8,8-tetracyano-p-benzoquinone dimethane with silver nitrate is 2-6 hours.

[0013] The above-mentioned graphene-based dynamic gas diffusion catalytic electrode material is combined with a polytetrafluoroethylene membrane to form a catalytic electrode.

[0014] The purpose of using the catalytic electrode for the electrocatalytic synthesis of hydrogen peroxide.

[0015] The electrolytic cell used is a flow electrolytic cell, and the electrolyte flow rate is 20-80 mL / min. -1 The oxygen flow rate is 20-60 mL / min. -1 The energy sources used are electric drive and photovoltaic drive.

[0016] Compared with the prior art, the advantages of this invention are: (1) The electrode is composed of 0D MOF nanodots (Ag-TCNQ) and 3D graphene hydrogel to form a dynamic gas diffusion electrode. The preparation method is simple and can be mass-produced industrially; (2) The introduction of low-dimensional nanomaterials (such as graphene and quantum dots) provides high specific surface area and abundant active sites; (3) The microstructure of the gas diffusion electrode can be adjusted by the evaporation, shrinkage, solvent retention and related capillary force interactions of water; (4) The device is driven by photovoltaics, the device structure is simple and easy to expand applications. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the synthetic route for preparing the composite material and graphene-based dynamic gas diffusion catalytic electrode of the present invention.

[0018] Figure 2 Figure 1 shows SEM images of the catalysts prepared in Comparative Example 1(a), Example 1(b), Comparative Example 2(c), Comparative Example 3(d), and Comparative Example 4(e) of this invention. Figure 2(f) shows the changes in density and average pore size of the dynamic gas diffusion electrode in Example 1 and Comparative Examples 1-4 with NMP content.

[0019] Figure 3 These are photographs of corresponding examples of the catalysts prepared in Example 1 and Comparative Examples 1-4 of this invention.

[0020] Figure 4 (a) is a TEM image of Embodiment 1 of the present invention, (b) is an HR-TEM image of Embodiment 1 of the present invention, and (c) is an AFM image of Embodiment 1 of the present invention.

[0021] Figure 5 (a) is the infrared spectrum (FT-IR) of Example 1 and Comparative Example 5 of the present invention, and (b) is the Raman spectrum of Example 1 and Comparative Example 6 of the present invention.

[0022] Figure 6 These are the XRD patterns of Comparative Examples 1, 2 and Example 1 of the present invention.

[0023] Figure 7 This is the X-ray photoelectron spectroscopy (XPS) of Embodiment 1 of the present invention.

[0024] Figure 8 The LSV curves (a) and corresponding KL diagrams (b) of the RRDE of the material in Example 1 of this invention at different rotational speeds are shown.

[0025] Figure 9 This is a diagram of a liquid flow electrolysis cell apparatus used in the electrocatalytic production of hydrogen peroxide with the material of Embodiment 1 of the present invention.

[0026] Figure 10This is a schematic diagram (a) of the internal structure of the liquid flow electrolysis cell used in the electrocatalytic production of hydrogen peroxide with the material of Example 1 of the present invention, a physical diagram (b) of the liquid flow electrolysis cell system and a diagram (c) of the electrodes used.

[0027] Figure 11 The diagram shows the it curve (a) of the material in Example 1 of this invention under different applied potentials in a flow battery and the corresponding hydrogen peroxide production graph (b).

[0028] Figure 12 (a) is the material of Example 1 and Comparative Examples 1-4 of the present invention at 0.267 V ( vs (a) is a graph showing the H2O2 yield and Faraday efficiency of the material in Example 1 of this invention at 0.267 V (RHE). vs A 10-hour stability test was conducted under RHE conditions. The inset shows the LSV curves before and after the stability test.

[0029] Figure 13 This is a schematic diagram (a) of the photovoltaic-driven electrochemical oxygen reduction to generate H2O2 device of the present invention, and a graph (b) showing the H2O2 production and Faraday efficiency of the photovoltaic device at different times. Detailed Implementation

[0030] In nature, many chemical reactions can be activated by enzymes, which are highly hydrated structures composed of large amounts of water. During catalysis, the substructure can dynamically change according to different conditions. Therefore, it is necessary to construct hydrated electrodes with tunable pore structures for gas transport and to immobilize active sites within the gas diffusion electrode (GDE). Inspired by this phenomenon, we innovatively propose a graphene-based dynamic gas diffusion catalytic electrode composed of Ag-TCNQ nanodots on a graphene hydrogel. The structure of the hydrogel (water content >90%) can be effectively controlled by capillary forces, forming a series of dynamic gas diffusion catalytic electrodes with tunable pore structures, abundant active sites, and large specific surface areas. Using a polytetrafluoroethylene (PTFE) membrane and the above electrode combination, a stable three-phase interface is formed in a flow electrolyzer system. Notably, the dynamic GDE shows great promise for achieving record-breaking H2O2 production performance from ORR, while exhibiting excellent activity, selectivity, and robustness.

[0031] Example 1: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 30% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Remove the obtained material and allow it to evaporate in the air for 6 hours; Step 5: Dissolve 100 mg of 7,7,8,8-tetracyanobenzoquinone dimethane (TCNQ) in 10 mL of acetonitrile. Immerse the sample obtained in Step 4 in the above solution for 2 hours, and wash to obtain the composite material, denoted as 30% Ag-TCNQ / rGO.

[0032] Comparative Example 1: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 0% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Remove the obtained material and allow it to evaporate in the air for 6 hours; Step 5: Dissolve 100 mg of 7,7,8,8-tetracyanobenzoquinone dimethane (TCNQ) in 10 mL of acetonitrile. Immerse the sample obtained in Step 4 in the above solution for 2 hours, and wash to obtain the composite material, denoted as 0% Ag-TCNQ / rGO.

[0033] Comparative Example 2: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 50% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Remove the obtained material and allow it to evaporate in the air for 6 hours; Step 5: Dissolve 100 mg of 7,7,8,8-tetracyanobenzoquinone dimethane (TCNQ) in 10 mL of acetonitrile. Immerse the sample obtained in Step 4 in the above solution for 2 hours, and wash to obtain the composite material, denoted as 50% Ag-TCNQ / rGO.

[0034] Comparative Example 3: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 70% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Remove the obtained material and allow it to evaporate in the air for 6 hours; Step 5: Dissolve 100 mg of 7,7,8,8-tetracyano-p-benzoquinone dimethane (TCNQ) in 10 mL of acetonitrile. Immerse the sample obtained in Step 4 in the above solution for 2 hours, and wash to obtain the composite material, denoted as 70% Ag-TCNQ / rGO.

[0035] Comparative Example 4: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 100% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Remove the obtained material and allow it to evaporate in the air for 6 hours; Step 5: Dissolve 100 mg of 7,7,8,8-tetracyanobenzoquinone dimethane (TCNQ) in 10 mL of acetonitrile. Immerse the sample obtained in Step 4 in the above solution for 2 hours, and wash to obtain the composite material, denoted as 100% Ag-TCNQ / rGO.

[0036] Comparative Example 5: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Place the obtained sample in a 30% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 3: Take out the obtained material, place it in the air to evaporate for 6 hours, wash it to obtain the composite material, and record it as 30%rGO.

[0037] Comparative Example 6: Step 1: Add 2.5 mL of graphite oxide (GO, 2 mg / mL) to the solution. -1 The mixture was mixed with a carbon cloth substrate and hydrothermally treated at 150°C for 6 hours to form an rGO hydrogel. Step 2: Add 200 mg AgNO3 to a mixed solution of deionized water (1 mL) and N-methylpyrrolidone (NMP, 19 mL) to prepare a silver nitrate solution. Place the rGO hydrogel in the silver nitrate solution and react for 4 hours to produce a silver nanoparticle / reduced graphene oxide hydrogel hybrid (represented as Ag-rGO). Step 3: Place the obtained sample in a 30% NMP / H2O (v / v) mixed solution for 3 h for displacement; Step 4: Take out the obtained material, let it evaporate in the air for 6 hours, wash it to obtain the composite material, and record it as 30%Ag / rGO.

[0038] The SEM image of the gas diffusion electrode obtained in Example 1 is shown below. Figure 2 As shown in (b), compared with Comparative Example 4 ( Figure 2 (e) Compared to the previous method, the material pore diameter was significantly reduced, and the material density increased to 136.55 mg / cm³. -3 The average pore size decreased from 1,750 nm to 475 nm. This was achieved when the volatile solvent was 0%. Figure 2 (a) Comparative Example 1 shows that the pores of the material shrink to near closure due to capillary forces, at which point the material density reaches its maximum of 446.07 mg / cm³. -3 .

[0039] The solvation and electrostatic repulsion between graphene oxide particles ensure that the structures in the graphene hydrogel remain largely separated, resulting in an ultra-high specific surface area. However, the formed graphene hydrogel has a low density (56.81 mg / cm³). -3 This results in mediocre catalytic performance. When the non-volatile solvent accounts for 30%, the dynamic gas diffusion electrode exhibits a dense porous structure, and the packing density can be increased to 136.55 mg cm⁻¹. -3 The dynamic gas diffusion electrode exhibits the highest packing density (446.07 mg / cm³) when the non-volatile solvent content is 0%. -3 However, graphene's adaptive self-assembly behavior will continue to shrink the pores until they are completely closed, encapsulating the active site Ag-TCNQ, resulting in a decrease in surface area and electrocatalytic activity.

[0040] Figure 4 Figures 5 and 6 clearly show the presence of the two-dimensional graphene sheets and Ag-TCNQ nanodots in Example 1, with an average size of 5-7 nm. Figure 5 As shown in (a), when silver binds to the organic ligand (TCNQ), new peaks appear in the Fourier transform infrared (FTIR) spectrum (corresponding to C≡N, C=C, and CH), indicating the formation of Ag-TCNQ MOFs on the rGO surface. However, due to their trace amounts, the peak intensity is weak and difficult to identify. The binding of silver and TCNQ can be further clearly demonstrated by Raman spectroscopy.

[0041] Typically, silver nanoparticles exhibit strong Raman enhancement, which disappears after interaction with TCNQ, further confirming the transformation from silver nanoparticles to Ag-TCNQ on the rGO surface. Figure 5 (b)). These results are consistent with those obtained by X-ray diffraction (XRD). Figure 6 (a) Consistent with X-ray diffraction, all characteristic peaks of Ag / rGO corresponding to silver nanoparticles were observed. With the addition of TCNQ ligand, all characteristic peaks of silver gradually weakened, and some new diffraction peaks appeared. These new peaks can all be attributed to Ag-TCNQ ( Figure 6 (b)).

[0042] In addition, XPS ( Figure 7 The results indicate that Ag-TCNQ / rGO contains C (87.6%), O (10.96%), Ag (0.09%), and N (1.36%). In the Ag 3d spectrum of the 30% Ag-TCNQ / rGO hydrogel, a characteristic metallic Ag 3d band is observed at 367.90 eV. 5 / 2The binding energy (BE) signal indicates the presence of residual Ag in Ag-TCNQ / rGO. Compared to the characteristic peak of elemental Ag, the peak values ​​shift significantly from 373.59 eV to 373.90 eV and from 367.59 eV to 368.70 eV. Furthermore, the XPS of 30% Ag-TCNQ / rGO also shows additionally important peak positions at 368.70 eV and 373.90 eV, corresponding to Ag... + Ions and TCNQ - Complexation was observed, further confirming the formation of Ag-TCNQ nanodots. On the other hand, the N 1s spectrum decomposed into three peaks: pyridine nitrogen (397.8 eV), pyrrole nitrogen (400.0 eV), and graphitic nitrogen (401.5 eV).

[0043] For the rotating disk electrode, LSV was collected in O2-saturated electrolyte at 900–3600 rpm and iR correction was performed. The electron transfer number was calculated based on the Koutecky-Levich method, and the electron transfer number was approximately 1.93 ( Figure 8 Its performance was quantified by it testing at different potentials. Figure 11 The result was shown at 0.267 V ( vs Under RHE conditions, the maximum H2O2 yield was obtained at 5.572 mol g. cat. -1 h -1 And 86.4% FE.

[0044] Furthermore, we systematically investigated the influence of porosity in dynamic GDEs on ORR performance. For example... Figure 12 As shown in (a), when the NMP component in the dynamic gas diffusion electrode is 30%, the H2O2 yield can reach 5.57 mol g. cat. -1 h -1 The yields were superior to other ratios, such as 0%, 50%, 70%, and 100%, corresponding to 4.36, 4.85, 4.65, and 4.66 mol g, respectively. cat. -1 h -1 (Approximately 20% improvement). The performance improvement is due to its dense porous structure, which provides oxygen transport channels and longer retention times, thereby increasing yield and utilization. This novel electrochemical device can operate stably for an extended period of 10 hours. Figure 12 (b)).

[0045] like Figure 13As shown in (a), to verify the concept of directly generating H2O2 from water, O2, and sunlight, we connected the aforementioned flow electrolyzer to a commercial silicon solar cell (energy conversion efficiency = 19%, peak voltage = 1.6 V). Under simulated sunlight, the system achieved a voltage of 12 mA cm⁻¹. -2 The current density (without iR correction). Furthermore, as... Figure 13 As shown in (b), the photovoltaic electrochemical system can operate for more than 3 hours under simulated sunlight, with an FE of 75% and a yield of 2550 mmol g. cat. -1 h -1 Further quantification of the product showed that the efficiency of solar energy to hydrogen peroxide was 14.8%, indicating that the system has good prospects for industrial application.

Claims

1. A method for preparing a graphene-based dynamic gas diffusion catalytic electrode material, characterized in that, Includes the following steps: Step 1: Prepare graphene hydrogel by hydrothermal reduction of graphene oxide ink solution on a substrate for gas diffusion electrodes; Step 2: Place the graphene hydrogel obtained in Step 1 in a silver nitrate aqueous solution of a certain concentration and react for a period of time. Step 3: Place the sample obtained in Step 2 in an N-methylpyrrolidone / water mixed solution and react for a period of time. The volume ratio of N-methylpyrrolidone to water in the N-methylpyrrolidone / water mixed solution is 3 / 7. Step 4: Place the material obtained in Step 3 in the air to evaporate for a period of time; Step 5: Place the material obtained in Step 4 into an acetonitrile solution, add an acetonitrile solution of the organic ligand 7,7,8,8-tetracyano-p-benzoquinone dimethane, and continue to let the reaction stand for a period of time to obtain a graphene-based dynamic gas diffusion catalytic electrode material.

2. The method as described in claim 1, characterized in that, In step one, the hydrothermal reduction reaction temperature is 140-160 ℃, and the reaction time is 4-8 h.

3. The method as described in claim 1, characterized in that, In step one, the substrate for the gas diffusion electrode includes carbon cloth and carbon felt.

4. The method as described in claim 1, characterized in that, In step two, the concentration of the silver nitrate aqueous solution is 10 mg / mL. -1 The reaction time is 2-8 hours.

5. The method as described in claim 1, characterized in that, In step two, the mass ratio of graphite oxide to silver nitrate is 1:40-1:

60.

6. The method as described in claim 1, characterized in that, In step three, the reaction time is 2-4 hours.

7. The method as described in claim 1, characterized in that, In step four, the evaporation time is 5-12 hours and the temperature is 15-35℃.

8. The method as described in claim 1, characterized in that, In step five, the reaction time is 2-6 hours.

9. The graphene-based dynamic gas diffusion catalytic electrode material prepared by the method according to any one of claims 1-8.

10. The use of the graphene-based dynamic gas diffusion catalytic electrode material prepared by the method according to any one of claims 1-8 for the electrocatalytic synthesis of hydrogen peroxide.